On the Merits of Meritocracy - John Morgan; Dana Sisak; Felix Vardy (Tinbergen Institute, 2012)
We study career choice when competition for promotion is a contest. A more meritocratic profession always succeeds in attracting the highest ability types, whereas a profession with superior promotion benefits attracts high types only if the hazard rate of the noise in performance evaluation is strictly increasing. Raising promotion opportunities produces no systematic effect on the talent distribution, while a higher base wage attracts talent only if total promotion opportunities are sufficiently plentiful.
urn:NBN:nl:ui:15-1765/34712
Keywords: J45; J24; M52; 330; career choice; promotion competition; selection; meritocracy; Politiker; Erwerbsverlauf; Wahlkampf; Neue politische Ökonomie; Theorie